"Basic education assistance module as a material and psychosocial support intervention for orphans and vulnerable children in Gutu District, Zimbabwe. An evaluation". (December 2020) - Ringson, John
Abstract: Much has been written on the psychosocial support of orphans and vulnerable children (OVC) around the world regarding their well-being. However, there is still a lack of information on the efficacy of the Basic Education Assistance Module (BEAM) both as material and a psychosocial support intervention for OVCs within the rural communities of Zimbabwe. This article is a qualitative phenomenological study seeking to examine the perceptions, views and feelings of the OVC, care-givers and community leaders on their experiences with BEAM as a material and psychosocial support intervention in Zimbabwe. In-depth interviews were conducted with 10 OVCs which consist of the primary and secondary school going children; 10 care-givers and 10 community leaders purposively selected in the Gutu District of Zimbabwe. The results showed that whilst the BEAM has been applauded as an OVC psychosocial support intervention, its efficacy was marred by its failure to proportionately and holistically provide all the basic needs of the school-going OVCs within the rural communities. This study therefore recommends the establishment of the OVC stakeholders integrated support model, which is deeply entrenched in a holistic approach for the provision of the material and psychosocial support needs of the OVCs in Zimbabwe.